PENGGUNAAN CARIES RISK ASSESSMENT AND REFERRAL TOOL (CRA- RT) PADA KARIES DINI ANAK - siti hajar leni siregar; atik ramadhani; Melissa adiatman (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Early childhood caries severity assessment requires a concise, simple, and reliable instrument, incorporate the factors involved in the development of caries in childhood. Caries Risk Assessment and Referral Tool instrument can be used to assess caries risk scores without clinical examination and used by dentists in planning further treatment. Methods: Literature searches were conducted in the PubMed/Medline and Science Direct databases published from 2019 to 2022 on caries risk assessment, early childhood caries, and referral tools. Results: Based on a search on PubMed, 118 journals were found, and 125 journals were found on Science Direct. 23 journals were discovered after journals were filtered by title and exclusion criteria. Furthermore, additional 28 journals were added as references with a manual search method. Conclusion: CRA-RT is very helpful, especially during a pandemic with minimal clinical examinations. It is quite simple and can be used by non- dental or non-medical personnel. So that cases of ECC are easier to find, and can be treated to reduce the severity.